PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP ALOKASI BELANJA DAERAH - Ardiansyah, Oni (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out and to prove empirically the influence of Local Own Source Revenue (PAD) and General Allocation Funds (DAU) to the direct expenditure and indirect expenditure allocation at Mojokerto regency/city from 2011 to 2013. The research method is quantitative research method with secondary collection technique. The object of the research is realization report document of Local Government Budget (APBD) of Mojokerto regency/city which has been obtained from Directorate General of Local Government Fiscal Balance website in the internet from 2011 to 2013. Based on the result of F-test gains the adequate result of regression model since the whole Local Own Source Revenue variable and General Allocation Fund can explain to the direct expenditure and indirect expenditure allocation at Mojokerto regency/city. The result of t-test at indirect expenditure allocation shows the opposite result. While the determination coefficient value (R2) which has been showed by Adjusted R2 gains result 0.932 or 93,2% shows that Local Own Source Revenue and General Allocation Fund can explain Direct Expenditure Fund variable 93%. While the influence of the Local Own Source Revenue and General Allocation Fund to the Indirect Expenditure Allocation from correlation coefficient (R) is 0.995 or 99.5%.Keywords: Local Own Source Revenue (PAD), General Allocation Fund (DAU), Direct Expenditure Allocation (ABL), and Indirect Expenditure Allocation (ABTL)